Predicting the Potential Mechanism of Radix Sophorae Flavescentis Treating Hepatocellular Carcinoma Based on the Strategies of Network Pharmacology, Molecular Docking, and Molecular Dynamics Simulation - Hong, Jing; Ding, Jie; Wang, Peng; Zhai, Xiao-Feng; Pan, Bo (Letters in Drug Design & Discovery, 2024)
Background and ObjectiveHepatocellular carcinoma (HCC) is a common hepatic malignant tumor severely affecting the life and health of people globally. Radix Sophorae Flavescentis (RSF) is a Chinese herbal medicine widely utilized in China. However, its main ingredients and mechanism have not been fully illustrated. The current study explored the potential mechanism of RSF treating HCC through network pharmacology, molecular docking, and molecular dynamics simulation.Materials and MethodsThe potential RSF active compounds and the corresponding targets were retrieved from TCMSP, TCMID, HERB, ETCM, and BATMAN-TCM databases. HCC-related target genes were primarily mined using GeneCards and OMIM databases. The intersection target genes of RSF and HCC were collected, and the protein-protein interaction (PPI) network was constructed to obtain the core target genes of RSF in HCC. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed on the core targets. The network analysis results were verified through molecular docking and molecular dynamics simulation using active compounds and core targets.ResultsIn this study, 23 potentially active ingredients of RSF and 203 corresponding targets of the active ingredients were mined, and 4594 HCC-related target genes were finally identified. Thereinto, quercetin, luteolin, formononetin, and 8-isopentenyl-kaempferol were predicted to be the core targets, and 61 core targets such as TP53, JUN, HSP90AA1, AKT1, MAPK1, RELA, TNF, and ESR1 were further screened through PPI network analysis. GO enrichment and KEGG pathway analysis revealed that the treatment of HCC with RSF mainly involved the receptor signaling pathway of vascular endothelial growth factor, cytoplasm, protein domain specific binding, and other biological processes. Signaling pathways included pathways in cancer, Hepatitis B, IL-17 signaling pathway, etc. Molecular docking and molecular dynamics simulations validated the above results.ConclusionThis study elucidated the potential mechanism of RSF in the HCC treatment through network pharmacology, molecular docking, and molecular dynamics simulation, thereby offering valuable insights for future clinical investigations.
Keywords: radix sophorae flavescentis